Novel 3-fluoro-4-morpholinoaniline derivatives: synthesis and assessment of anti-cancer activity in breast cancer cells - More, Namita A.; Jadhao, Nitin L.; Meshram, Rohan J.; Tambe, Prajakta; Salve, Rajesh A.; Sabane, Jagjivan K.; Sawant, Sanskruti N.; Gajbhiye, Virendra; Gajbhiye, Jayant M. (Journal of Molecular Structure, 2022)
Heterocyclic morpholine compounds are well-known for their anti-cancer activity. In this study, novel morpholine and its sulfonamide derivatives were designed and synthesized as potential anti-tumor agents. The new compounds were obtained from amine derivatives via nucleophilic addition reactions, providing the desired products in 70 to 90% yield. The docking analysis was performed for all thirty-one compounds. Out of them, we represent the docking poses for compounds NAM-5 and NAM-7 as representatives. After docking analysis, compounds NAM-5 and NAM- 7 were tested for in vitro antitumor activity against breast cancer cell lines (MCF-7 and MDA-MB-231) and healthy mouse embryonic fibroblast cell line (3T3L-1). Amongst these, sulfonamide group-containing compound NAM-5 showed significant anti-proliferative activity with IC50 of 1.811 mu M and 2.143 mu M for MCF-7 and MDA-MB-231 cells, respectively. On the other hand, NAM-7 showed good anti-proliferative activity against MCF-7 (IC50 1.883 mu M) but slightly lower activity against MDA-MB-231 cells (IC50 4.688 mu M). The activity of both the compound was also tested on 3T3L-1 Cell line which showed activity similar to clinically approved anti-cancer drug doxorubicin (DOX). The cell death analysis by flow-cytometry confirmed apoptosis mediated cell death in 3T3L-1, MCF-7 and MDA-MB-231 cells when treated with the NAM-5 and NAM-7, respectively. The results demonstrated that the synthesized sulfonamide derivatives have significant potential as anti-cancer agents and have a substantial importance in cancer therapeutics with favourable safety profile. Structural analysis of docked poses of sulfonamide derivatives attempts to shed light on the structural basis of sulfonamide derivatives based anti-cancer effect. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Anticancer activity; Apoptosis; Breast cancer; Heterocyclic compounds; Morpholine; Sulfonamide

Copper-mediated [3+2] oxidative cyclization of oxime acetate and its utility in the formal synthesis of fentiazac - Jadhao, Nitin L.; Musale, Harish B.; Gajbhiye, Jayant M.; Humne, Vivek T. (Organic and biomolecular chemistry, 2024)
A new protocol for the direct synthesis of 2-aminothiazole has been developed from oxime acetate and readily available sodium thiocyanate using a copper catalyst. The present transformation has good functional group tolerance. Various thiazoles were smoothly synthesized in good to excellent yields. The applicability of the present method has been extended to the formal synthesis of the non-steroidal and anti-inflammatory drug, fentiazac via the Sandmeyer reaction and Suzuki coupling. The direct synthesis of 2-aminothiazole has been developed from oxime acetate using a copper catalyst. The applicability of the present method is used in the formal synthesis of fentiazac.
Keywords: Biological evaluation; C-H functionalization; Vinylazides

Synthesis of pyrazole and 1,3,4-oxadiazole derivatives of pharmaceutical potential - Kadam, Mayur; Jadhao, Nitin L.; Gajbhiye, Jayant M. (Prospects in Pharmaceutical Sciences, 2024)
Heterocyclic compounds are important molecules that serve as scaffolds or linkers for the core structure of numerous drug substances. In particular, pyrazole and 1,3,4-oxadiazole are compounds of great interest due to their comprehensive biological activities and interesting structural features. Here, we described an efficient and economical synthetic route leading to N-phenyl substituted pyrazole and 1,3,4-oxadiazole derivatives. Retrosynthetic disconnective analysis showed that the N-phenyl substituted pyrazole can be obtained from chalcone, accessible from the respective aldehyde, and acetophenone. The disubstituted 1,3,4-oxadiazole can be constructed from the respective aldehyde, which originates from pyrrole-containing compound, and formyl chloride. Based on our retrosynthetic analysis, N-phenyl substituted pyrazole was obtained by cyclization of the respective chalcone with phenylhydrazine to give pyrazoline which was in turn converted into pyrazole by oxidative aromatization. Potassium carbonate and a catalytic amount of molecular iodine were used to oxidatively cyclize semicarbazones into 1,3,4-oxadiazoles in a transition metal-free process. Novel pyrazole and 1,3,4-oxadiazoles with potential biological activity are investigated as antituberculosis, anticonvulsant, antidiabetic, anticancer, and tyrosinase inhibitory agents.

Synthesized novel chromogenic reagent and sensor: detection and identification of dichlorvos - Gedam, Ashwin D.; Katiya, Manish M.; Dhonde, Madhukar G.; Ganorkar, Kapil S.; Thakare, Vijay J.; Mandlik, Prashant R.; Jadhao, Nitin L.; Gajbhiye, Jayant M.; Kumar, Ravi; Vaval, Nayana (Heliyon, 2024)
We developed a novel chromogenic reagent and sensor by selective approach, for the detection and identification of dichlorvos, which we tested with the thin layer chromatography method. For the first time, we reported in situ-generated glyoxal as a hydrolysis product, which then interacts with isoniazid to produce a yellow-colored cyclic compound. We used well-known spectroscopic techniques to confirm the chemical identity of the final product. We initially investigated the reaction using a variety of approaches, followed by attempts to establish the reaction mechanism using Density Functional Theory by Gaussian software.
Keywords: DFT analysis; Dichlorvos; Gloyxal; Hydrazone; Isoniazid

Aqueous-mediated selective reduction of Imidacloprid: a novel method for detoxification and detection - Gedam, Ashwin D.; Katiya, Manish M.; Dhonde, Madhukar G.; Ganorkar, Kapil S.; Thakare, Vijay J.; Jadhao, Nitin L.; Gajbhiye, Jayant M. (Journal of Environmental Chemical Engineering, 2026)
The extensive application of the neonicotinoid insecticide Imidacloprid has produced significant environmental concerns owing to its persistence and toxicity in aquatic ecosystems, thereby necessitating the development of straightforward and environmentally sustainable methods for its detection and detoxification. In the present study, we demonstrate for the first time that selective reducing agents can function as environmentally friendly chromogenic reagents for the detoxification and detection of Imidacloprid in contaminated water. The insecticide was treated with various reducing agents, such as aqueous solution of glucose, sodium sulphite, hydrazine hydrate, isoniazid, and vanillin, leading to the reduction of Imidacloprid and the formation of a white solid product. The reaction process provides a straightforward visual indication, suggesting the possible use of these reagents as eco-friendly chromogenic systems for pesticide monitoring. The chemical identification and structural properties of the resultant product were elucidated and confirmed by standard spectroscopy techniques. Moreover, the reaction pathway was systematically examined through experimental observations and theoretical studies. Density Functional Theory (DFT) calculations were conducted with the Gaussian program to provide a more profound understanding of the reaction pathway. The integrated experimental and computational findings offer a reliable mechanistic insight into the reduction process and highlight the potential of selective reducing agents as environmentally friendly reagents for the detection and detoxification of Imidacloprid in aquatic ecosystems.
Keywords: DFT analysis; Extracted Imidacloprid; glucose; Hydrazine hydrate; Isoniazid; Sodium sulphite; Vaniline